Application of acupuncture in treating decreasing libido in the menopausal stage - Woźniak, Piotr; Ziółkowski, Paweł; Stetkiewicz, Tomasz; Pięta-Dolińska, Agnieszka; Oszukowski, Przemysław (Menopause Review/Przegląd Menopauzalny, 2011)
Menopause of Polish women occurs approximately between 48 and 52 years of life. It is a time of many disorders in the woman’s organism, which not only affect the health but also deteriorate the quality of life. One of the symptoms of menopause, very frequently “bashfully unsaid”, is the occurrence of decreasing libido among the patients. Despite the fact of hormonal replacement therapy (HRT) in treating symptoms of near menopausal stage, some of the women still suffer the decrease of libido. Acupuncture as an element of traditional Chinese medicine (TCM) has been in use for thousands of years in therapy of many different chronic illnesses. Since a couple of years ago once more we have been using it in menopause therapy. This article describes the impact of use of acupuncture procedures on level of libido in a group of 24 women aged 54-56. We observed a beneficial impact of acupuncture procedures both on the increasing level of libido and in the improvement of women’s life after the treatment because of the profitable influence of acupuncture on different symptoms of climacteric syndrome (hot flashes, night sweats, sleeping disorder, depression).